2019
DOI: 10.1080/00273171.2019.1634995
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Block Distance-Association Model for Profile by Profile Cross-Classified Categorical Data

Abstract: Distance association models constitute a useful tool for the analysis and graphical representation of cross-classified data in which distances between points inversely describe the association between two categorical variables. When the number of cells is large and the data counts result in sparse tables, the combination of clustering and representation reduces the number of parameters to be estimated and facilitates interpretation. In this article, a latent block distance-association model is proposed to appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…We also illustrate the performance of the model in a person‐oriented approach to data analysis, focusing on the personal profiles of the categorical variables (Bergman & Magnusson, 1997). To do so, we considered a personality data set (Spinhoven, de Rooij, Heiser, Penninx, & Smit, 2009) that was previously analysed, taking a person‐oriented approach, by Vera and de Rooij (2020) for sparse tables. In this paper, we analyse a non‐sparse data set in which the row profiles are based on the personality variables of Agreeableness and Conscientiousness, while the column profiles are cross‐classifications of the four mental disorders Major Depressive Disorder, Generalized Anxiety Disorder, Social Phobia, and Panic Disorder.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also illustrate the performance of the model in a person‐oriented approach to data analysis, focusing on the personal profiles of the categorical variables (Bergman & Magnusson, 1997). To do so, we considered a personality data set (Spinhoven, de Rooij, Heiser, Penninx, & Smit, 2009) that was previously analysed, taking a person‐oriented approach, by Vera and de Rooij (2020) for sparse tables. In this paper, we analyse a non‐sparse data set in which the row profiles are based on the personality variables of Agreeableness and Conscientiousness, while the column profiles are cross‐classifications of the four mental disorders Major Depressive Disorder, Generalized Anxiety Disorder, Social Phobia, and Panic Disorder.…”
Section: Resultsmentioning
confidence: 99%
“…However, in this case the association plot may be difficult to interpret due to the presence of a large number of points (profiles). In this framework, a practical alternative is to combine latent class models (Vera, de Rooij, & Heiser, 2014) and latent block models (Vera & de Rooij, 2020), in conjunction with DA models. This approach makes it possible to represent associations in relation to the estimated clusters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an interesting case is when several categorical explanatory variables are combined to conform a large number of profiles. [40][41][42] In this situation, the combination of categories forming the profiles causes a large number of auxiliary variables to emerge after recoding using dummy variables, and a problem of over-calibration may arise in this qualitative information framework. Other methods for selecting the optimal set of variables are also being investigated, in particular, related to combined MDS and cluster methods that allow reducing dimensionality.…”
Section: Discussionmentioning
confidence: 99%
“…Distance association (DA) models enable the representation of associations for a saturated log‐linear model in terms of squared Euclidean distances 2‐4 . It has been shown that the DA model produces the same expected frequencies than the RC(M) model, 5 although the graphical interpretation of the associations is easier in the DA model in terms of points in a Euclidean space 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In low dimensions, the distance association model is an approximation to the traditional log‐linear model and, in general, it is more efficient than a two‐step procedure that first performs traditional log‐linear analysis and then represents the associations in terms of Euclidean distances. In a combined procedure of clustering and distance association model to deal with sparse data sets, the superiority of a simultaneous strategy compared to a two‐step procedure has been explicitly shown by Vera, de Rooij and Heiser 3 for the latent class distance association model and by Vera and de Rooij 4 for the latent block distance association model.…”
Section: Introductionmentioning
confidence: 99%